Evaluasi Penerapan Harga Transfer di PT Reebonz - Ade Suryana (Neraca : Jurnal Akuntansi Terapan, 2021)
This study aims to evaluate the transfer pricing activities of the transfer pricing practice conducted by PT Reebonz (“PT RB”) and its affiliates which are companies operating in a country with a lower tax rate than Indonesia in connection with compliance with the arm's length principle. This evaluation is carried out by analyzing the price setting which is measured based on Transactional Net Margin Method (TNMM) of independent comparison companies with the characteristics of similar industries to be compared with the net margin of PT RBI. This study used a qualitative method with a case study approach with data collection methods using interviews and documentation of data obtained from PT RB and data collection from the Bureau Van Dijk ("BVD") Database ("Oriana") external database. The results showed that the pricing measured based on the level of profitability of PT RB was within the interquartile range, so it could be concluded that PT RB had fulfilled the arm's length principle based on the taxation standards applicable in Indonesia. The research results are expected to be useful to increase understanding of the taxation aspects of setting transfer prices for affiliated transactions and their application to companies that carry out business activities in Indonesia and become a reference in setting transfer prices in conducting affiliate transactions for companies engaged in similar industrial sectors.